2008
DOI: 10.5191/jiaee.2008.15103
|View full text |Cite
|
Sign up to set email alerts
|

Education for Rural People: What have we learned?

Abstract: This article presents a synthesis of lessons learned since the launch of Education for Rural People (ERP) in 2002 under the leadership of the Food and Agriculture Organization (FAO) of the United Nations as part of the implementation process for the Millennium Development Goals (MDGs). The ERP program originated from the global consensus on the importance of education in reducing poverty and concern over the development challenges presented by approximately 880 million illiterate youth and adults and approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
0
0
1
Order By: Relevance
“…Some farmers stated that unsuitable schedule of extension events decreased their participation in extension activities (Altarawneh et al 2012). Acker and Gasperini (2008) reported a new set of knowledge and skills that rural people seek in extension programs. Skills regarding self-employment, food supply, and life skills became more popular among rural communities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some farmers stated that unsuitable schedule of extension events decreased their participation in extension activities (Altarawneh et al 2012). Acker and Gasperini (2008) reported a new set of knowledge and skills that rural people seek in extension programs. Skills regarding self-employment, food supply, and life skills became more popular among rural communities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While some of the barriers are related to the program planning, other barriers related to extension agents' competencies. (Acker 2008) mentioned that lack of relevance, flexibility, and local input may negatively impact the local engagement with programs. Washburn et al (2017) indicated that the effective extension agent shout be a facilitator that helps clients to set and reach their learning goals.…”
Section: Non-agricultural Activitiesmentioning
confidence: 99%
“…Por lo anterior, se considera necesario explorar estas problemáticas a través de la ciencia y la práctica docente, pues diferentes estudios (Aranda, 2008;Cazaux, 2008;Aldana, 2012;Narro y Moctezuma, 2012;Díaz y Alemán, 2008) permiten constatar que la ciencia, la tecnología, la Artículos de investigación educación y, particularmente, la acción docente contribuyen al desarrollo social, cultural y, desde luego, educativo de las naciones, además de que la labor del docente puede representar una estrategia para combatir la pobreza (Acker y Gasperini, 2009).…”
Section: Planteamiento Del Problemaunclassified